Curriculum Innovation and Design to Enhance Global Competence and Holistic Student Development - Iryna Voloodymyrivna Shevchenko (PT. Islamic Research Publisher, 2025)
This study explores curriculum innovation and design to enhance students’ global competence and promote holistic development. Recognising the increasing demands of a rapidly globalising world, educational institutions are challenged to equip students not only with disciplinary knowledge but also with critical thinking, intercultural awareness, and socio-emotional skills. The research aims to identify effective curriculum strategies that foster both cognitive and non-cognitive competencies, thereby preparing learners for complex global challenges. A mixed-methods approach was employed, integrating qualitative analysis of curriculum frameworks and policy documents with quantitative evaluation of student outcomes across multiple higher education institutions. Data collection included in-depth interviews with curriculum developers, surveys of students’ perceived competencies, and analysis of academic performance indicators. The thematic analysis focused on key dimensions of global competence—such as cross-cultural communication, ethical reasoning, and adaptability—while also examining the integration of holistic educational practices, including character building, creativity, and well-being initiatives. Findings indicate that curricula emphasising interdisciplinary learning, experiential projects, and international collaboration significantly enhance students’ global awareness and interpersonal skills. Moreover, programs that embed reflective practices, mentorship, and co-curricular activities contribute to holistic development by fostering emotional resilience, ethical judgment, and lifelong learning dispositions. The study also highlights challenges in aligning institutional policies with innovative practices, emphasising the need for faculty development, resource allocation, and continuous assessment mechanisms. This research contributes to the academic discourse on curriculum design by providing empirical evidence and practical guidelines for cultivating globally competent and well-rounded graduates. It underscores the importance of integrated pedagogical approaches that balance knowledge acquisition, skill development, and personal growth, offering a model adaptable across diverse educational contexts. The findings inform policymakers, educators, and curriculum designers seeking to advance educational quality in alignment with 21st-century competencies.